Pentingnya Sistem Pelayanan Informasi Bagi Pemerintah Dan Publik (Studi Kasus Aplikasi Kaba Aia Perumda Padang) - Maiasnita, Yeni; Darwis, Yuliandre (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
Providing a good service to the community is one of the duties of government. This is regulated by law. The government is obliged to provide information and services to the community in a systematic way. Especially in the current era of digitalisation, people want services that are mobile because it makes it easier for people to exercise their rights and fulfil their obligations. Indeed, digital services are part of the innovation in providing better services to the community. Digital services that are mobile in nature provide convenience, are faster and more efficient. Because the public information service system in conventional form is notoriously slow, takes longer, makes a person expend more energy. Perumda, a government agency that provides clean water, is trying to meet the needs of the public information system by introducing the Kaba Aia application.